Дополнения и исправления к фауне комаров-лимопиид (Diptera, Limoniidae) Южных Курил и Южного Сахалина - Савченко, Е.Н. (Вестник зоологии, 1979)
An additional list of the limoniid-flies found recently on the Southern Kuriles and Southern Sakhalin is given. 23 species are new for the Iturup island. 2 — for the Shikotan and 7 species for the Southern Sakhalin. One species, Ormosia (Parormosia)? nippoalpina Al., is new for the Soviet Union. A new species Dicranota (Rhaphidolabis) complicata Sav. sp. n. from Sakhalin and Kunashir is described. The material is preserved at the Institute of Zoology, Ukrainian Academy of Sciences, Kiev.